2013
DOI: 10.1007/s00442-013-2634-7
|View full text |Cite
|
Sign up to set email alerts
|

Management intensity and vegetation complexity affect web-building spiders and their prey

Abstract: Agricultural management and vegetation complexity affect arthropod diversity and may alter trophic interactions between predators and their prey. Web-building spiders are abundant generalist predators and important natural enemies of pests. We analyzed how management intensity (tillage, cutting of the vegetation, grazing by cattle, and synthetic and organic inputs) and vegetation complexity (plant species richness, vegetation height, coverage, and density) affect rarefied richness and composition of web-buildi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
89
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 112 publications
(94 citation statements)
references
References 39 publications
4
89
0
1
Order By: Relevance
“…This confirms previous studies that have shown how arthropod predators are influenced by decreased tillage disturbance [9,34]. For example, spider colonization and establishment have been shown to be favoured under conservation tillage due to the higher soil environment stability and weed density, which promotes a deeper litter and more structurally complex vegetation [4,35]. Aphid parasitism rate showed, instead, no difference between tillage systems.…”
Section: (A) Effects Of Soil Management On Ecosystem Service Provisionsupporting
confidence: 88%
“…This confirms previous studies that have shown how arthropod predators are influenced by decreased tillage disturbance [9,34]. For example, spider colonization and establishment have been shown to be favoured under conservation tillage due to the higher soil environment stability and weed density, which promotes a deeper litter and more structurally complex vegetation [4,35]. Aphid parasitism rate showed, instead, no difference between tillage systems.…”
Section: (A) Effects Of Soil Management On Ecosystem Service Provisionsupporting
confidence: 88%
“…2B; see references in Food web structure is affected by resolution). Interaction strength is often unquantified (from Summerhayes andElton 1923 through Cohen et al 1990 to Wirta et al 2015b), inferred from sometimes limited and always laborious observations of direct attacks (Carnicer et al 2009) or through methods with an only indirect link to realized predation and consumption rates (Frost 1972;Nyffeler 1999;Diehl et al 2013;Majaneva et al 2014). …”
Section: Problems Encountered In Reconstructing Food Web Structurementioning
confidence: 99%
“…They encompass a wide range of foraging strategies and as such are differentially sensitive to variations in vegetation architecture and disturbance (Barriga et al 2010;Dielh et al 2013;Gibson et al 1992). Differences in foraging strategies are linked to vegetation structure and disturbance (Alderweireldt 1994;Bell et al 2001;Uetz 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Differences in foraging strategies are linked to vegetation structure and disturbance (Alderweireldt 1994;Bell et al 2001;Uetz 1991). Ground hunting species require a heterogeneous sward of open patches to search for prey and taller vegetation for refuge (Maelfait and De Keer 1990), whereas orb web weaving spiders select structurally complex vegetation that provides increased web anchorage points (Dielh et al 2013;Langellotto and Denno 2004;McNett and Rypstra 2000). The differences in foraging strategy, activity and substrate utilisation amongst species make grouping spiders into guilds a useful tool for examining functional differences among habitats (Corcuera et al 2015;Schweiger et al 2005).…”
Section: Introductionmentioning
confidence: 99%